Summer ground level ozone maximum in Slovakia in 2003 - BIČÁROVÁ, Svetlana; SOJÁKOVÁ, Michaela; BURDA, Cyril; FLEISCHER, Peter (Contributions to Geophysics and Geodesy, 2021)
Extraordinary high level of ozone pollution occurred in Slovakia in August 2003. Monitoring stations recorded the following maximal O3 concentrations: mean hourly values of 127 to 301 μg·m–3, mean daily values of 72 to 153 μg·m–3, mean monthly values of 47 to 124 μg·m–3. The ambient air quality standards were frequently exceeded at the SW lowlanded urban area in Bratislava and the mountain rural station Lomnický štít: alert threshold IH1h = 240 μg·m–3, – 6 times in Bratislava, information threshold IH1h = 180 μg·m–3, – 44 times in Bratislava, 8 times at Lomnický štít, total 69 times at all monitoring stations. The target value 8h mean IH8h = 120 μg·m–3, was exceeded also in Bratislava and Lomnický štít over more than 25 days. General comparison of mean daily O3 concentration of urban and rural stations shows that ozone level at the rural sites is higher than at the urban ones. The summer ozone maximum in August 2003 appears to be associated with special ozone production and distribution due to the unusual warm weather situation and the transport of abundant ozone precursors over Europe. The decreasing trend of NOx pollutant suggests the ozone and precursors transboundary transport into Slovakia.